A makeover for Dudley's Q+. Issue 5 (25th November 2021) - Glackin, Caroline; Altobello, Suzanne
Abstract : Theoretical basis: The Dudley Beauty case illustrates a contemporary branding, management and marketing challenge facing many companies that are 50 plus years old. Movahhed (2016) highlights the six elements to consider during brand strategy: the target audience, the brand promise, brand perception (past, current and future), brand values, brand voice and brand positioning. The times have changed with changing macroenvironmental factors including political, economic, sociological, technological, legal and other environmental (PESTLE) changes that affect a business but which the business does not directly control. Research methodology: The case is based upon an interview with Dudley Beauty CEO and President Ursula Dudley Oglesby and secondary sources. Case overview/synopsis: The "A Makeover for Dudley's Q+" case explores the challenges of a second-generation textured hair care and personal care company in the direct selling channel as it faces an aging market and changing business and economic environment. A Black-owned company, begun in 1967 by her parents, Dudley Beauty is led by the founders' daughter, Harvard College and Harvard Law School-educated, Ursula Dudley Oglesby. At over 50 years old, the company has continually created new textured hair products and has high brand awareness among older Black consumers but has not adequately addressed changing hair trends and shifting communication preferences of younger consumers. The company is at a critical point needing to reach a younger, larger market to survive. The business situation supports marketing, management, strategy, and/or entrepreneurship undergraduate students in understanding how macroenvironmental forces and internal structures affect businesses. Complexity academic level: This case is intended primarily for use by undergraduates in a variety of courses. It is suitable for courses in Principles of Marketing, Entrepreneurial Marketing, general Entrepreneurship and Marketing Strategy courses covering topics such as direct selling, the role of environmental factors in business, rebranding efforts using digital and social media marketing and women/minority business owners.